Pengaruh Iklan Internet Dan Promosi Penjualan Terhadap Keputusan Pembelian Pada Shopee Bagi Konsumen Kayuagung - Tutik Pebrianti; Aras Tulip; Arubina Bangsawan; Indah Mawarni; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
Competition requires business people to innovate so that the product do not experience saturation so sales will not decrease. One of effort to overcome competition is to increase promotion. This research aims to examine the influence of internet advertising and sales promotion to purchasing decisions on Shopee for kayuagung. the research was conducted on the Kayuagung. The study population was 64.123 people and 80 people were taken as samples. Data analysis techniques and hypothesis testing used are multiple linear regression, partial test (t test) and simultaneous test (F test). The results of this study indicate that simultaneous testing (F test) of internet advertising and sales promotion has a significant effect on purchasing decisions at Shopee. Then in the partial test (t test) internet advertising have an significant effect on purchasing decisions at Shopee. Partial sales promotion testing (t test) havean significant effect on purchasing decisions at Shopee. Adjudted R Square shows that internet advertising and sales promotion contribute 47% and the remaining 53% is influenced by other variables.